Bahasa Inggris - Putri Sheila Amalia; Afrizal Firman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This research is to investigate the function of trust as a mediating variable between purchase intention and electronic word-of-mouth, live streaming, customer experience, and promotion in Makassar, Indonesia. In the context of real-time online commerce, this research aims to clarify the relationship between consumers' confidence in interactive digital marketing activities and their subsequent purchase behavior. A structured survey was sent out to 173 customers who had with live-streaming commerce platform, and a quantitative research technique was used using SmartPLS 4.1. According to the results, there is a strong relationship between electronic word-of-mouth, live streaming, customer experience, and promotion and consumer trust. Trust in turn, serves as a critical mediating mechanism linking digital service interaction with purchase intention. According to the findings, trust is enhancing user engagement and behavioral intention within live streaming commerce platforms. Therefore, digital service providers are encouraged to build trust through interactive communication, transparency, and service authenticity.